2020
DOI: 10.2147/cmar.s269624
|View full text |Cite
|
Sign up to set email alerts
|

<p>Characteristics and Management of <em>TP53</em>-Mutated Diffuse Large B-Cell Lymphoma Patients</p>

Abstract: Background/Aim TP53 mutation is recognized as a negative prognostic factor for patients with diffuse large B-cell lymphoma (DLBCL). Here, we present the characteristics of TP53 mut DLBCL patients following investigation of the effect of a treatment approach on survival of TP53 mut DLBCL patients. Methods A total of 44 DLBCL patients with TP53 mut … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…In humans, mutations in the p53 gene occur in DLBCL patients (about 20%) and are identified in both GCB and ABC subtypes. 48 Whether LMP1 or LMP2A affects p53 mutations in DLBCL remains to be elucidated. Finally, frequent mutations in cellular genes such as ID3 and TCF3 are found in BL and associated with the induction of cell survival mediated by the BCR and the promotion of tumor proliferation through cell cycle transition activated by CDK4/6−cyclin D. 2,8 - 10,27,43 - 46 Mutations in these genes were not changed by LMP1 in our sequence analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, mutations in the p53 gene occur in DLBCL patients (about 20%) and are identified in both GCB and ABC subtypes. 48 Whether LMP1 or LMP2A affects p53 mutations in DLBCL remains to be elucidated. Finally, frequent mutations in cellular genes such as ID3 and TCF3 are found in BL and associated with the induction of cell survival mediated by the BCR and the promotion of tumor proliferation through cell cycle transition activated by CDK4/6−cyclin D. 2,8 - 10,27,43 - 46 Mutations in these genes were not changed by LMP1 in our sequence analysis.…”
Section: Discussionmentioning
confidence: 99%
“…TP53 mutations have been shown to be significantly associated with poor overall survival in DLBCL [ 38 , 39 ]. Clipson A et al [ 40 ] also found the significant association of TP53 mutation with poor overall survival in DLBCL with MYC translocation.…”
Section: Discussionmentioning
confidence: 99%
“…Sample sequencing was performed on a Next Seq500 Sequencer (Illumina, Hayward, CA, USA) with pair-end reads at Burning Rock Biotech (Guangzhou, China) or Geneplus-Beijing (Beijing, China). The detailed sequencing procedure was performed as described previously 14 , 15 , 31 .…”
Section: Methodsmentioning
confidence: 99%